Implementasi Kurikulum Muatan Lokal Dalam Proses Pembelajaran Aksara Arab Melayu Pada Kelas IV di MIS YPI Batang Kuis Sumatera Utara - Mursal Aziz; Nur Aisyah Dalimunte; Nikmah Mustika; Wilda Rahmayani Ritonga; Liza Umami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to analyze curriculum implementation in the Malay Arabic script learning process in class V at MIS YPI Batang Kuis using descriptive qualitative methods. The research method in this study was carried out using data collection techniques, namely interviews, documentation and observation. The objects of this research were 30 students in class IV MIS YPI Batang Kuis. The data collection technique in this research is equipped with tests and questionnaires which take place face to face with students. Data analysis methods include assessing writing test scores, calculating the percentage of reading ability, as well as evaluating overall results to understand the effectiveness of teaching Malay Arabic script. It is hoped that the findings from this research will provide a more comprehensive view regarding the implementation of the Malay Arabic script learning curriculum in the form of teaching strategies that best support Malay Arabic learning in class V MIS YPI Batang Kuis. The results of this research can be a reflection to improve existing teaching methods. By understanding the successes and challenges in the learning process, more effective strategies can be developed to improve students' understanding of the Malay Arabic script. It is hoped that the implications of this research can help prepare better curriculum and teaching guidelines and improve the quality of the Malay Arabic script learning process at a broader level.